Strategi Kepala Sekolah dalam Meningkatkan Literasi Membaca Siswa di SMA Negeri 1 Kota Kediri - Muhammad Rijal Mahfudh; Ali Imron (Faculty of Tarbiyah Institut Agama Islam Tribakti (IAIT) Kediri, 2020)
This study discusses how the potential for literacy needed by education. Students’ literacy ability is closely related to the guidance of reading skills analytically, critically, and reflectively. However, the fact of learning at school this time has not been able to realize it well. Principals as leaders and at the same time policyholders must have the right strategy. This is a great homework for all educational institutions in Indonesia, including in the city of Kediri. This research uses qualitative methods with descriptive approaches, data collection methods in the form of, observation, interviews, and documentation. Checking the validity of the data using triangulation. Data analysis through steps, compile, manage, and combine all data obtained from the field so that it becomes a conclusion. The results of the study show that the principal’s strategy in improving reading literacy is for students, first, the level of habituation. Second, student literacy is directed at religious reading literacy. Third, forming a literacy team. This has not been said to be maximum because the school has obstacles. First, student reading facilities are the only libraries. Second, the delay in students can make students’ abilities, skills and insights different from a student who is disciplined.